TURUS TAJAK: MEMPERKOKOH SOLIDARITAS DAN IDENTITAS DAYAK MAANYAN - kumpiady widen (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
Turus Tajak is the ethnic term that describes the process of customary wedding ceremony among the Maanyaan Dayak of Central Kalimantan. The Maanyaan is one of Dayak ethnic groups of Central Kalimantan who occupy East Barito Regency. Historical of past experience of the Maanyan’s struggle and difficult lives has strengthened their solidarity and ethnic identity as one big extended family. These solidarity and ethnic identity are obviously seen and illustrated in their social lives wherever they live. One of their customary ceremonies that is still maintained until now is customary wedding ceremony named Turus Tajak. Semantically, Turus means a post or a pole, and Tajak means to set up a post or a pole in the water or on the ground. Symbolically Turus Tajak means to set up a strong basement for the new married couples to start and build their new household. There are two conditions described in Turus Tajak ceremony. The invited audiences alternately come forward in front of the couples and gives voluntary contribution(sum amount of money) and short advices on how to get together as new couples as well as how to build a new household. Turus Tajak ceremony, culturally binds all the Maanyan to be a big extended family.